2016
DOI: 10.1101/069963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Easi-CRISPR: Efficient germline modification with long ssDNA donors

Abstract: CRISPR/Cas9 technology efficiently produces short insertions or deletions (indels) and can insert short exogenous sequences at Cas9 cut sites. However, targeting long inserts is still a major technical challenge. To overcome this challenge, we developed Easi-CRISPR (Efficient additions with ssDNA inserts-CRISPR), a method that uses long, in vitro-synthesized, single-stranded DNAs with 50-100 base homology arms as repair templates. We demonstrate that Easi-CRISPR can generate knock-in and floxed alleles in mice… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…We also successfully inserted a long donor fragment into the targeted locus using the i-GONAD method. Long ssDNA donors were prepared using the ivTRT method described in our highly efficient knock-in method, "Easi-CRISPR" [18][19][20] . Since a large amount of ssDNA is required for the i-GONAD experiment, we used the spin column-based nucleic acid purification instead of gel purification where loss of sample recovery is very high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also successfully inserted a long donor fragment into the targeted locus using the i-GONAD method. Long ssDNA donors were prepared using the ivTRT method described in our highly efficient knock-in method, "Easi-CRISPR" [18][19][20] . Since a large amount of ssDNA is required for the i-GONAD experiment, we used the spin column-based nucleic acid purification instead of gel purification where loss of sample recovery is very high.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that knocking-in of longer sequences can be efficiently achieved using ssDNA donors [18][19][20] . We tested whether long ssDNA donors can be used with i-GONAD to create knock-in alleles.…”
Section: ) Knocking-in Of Long Ssdna Donors Using I-gonadmentioning
confidence: 99%
“…Within the arthropods, crustaceans offer an interesting opportunity for Hox gene analysis, as they exhibit immense diversity, particularly in regards to limb morphology, yet have body regions that can be readily homologized (VanHook & Patel, ), at least within some clades. Crustacean Hox gene expression domains correlate with the presence of particular limb types, suggesting that AP body regionalization is controlled by Hox expression.…”
Section: Case Studiesmentioning
confidence: 99%
“…This is likely to be tolerated more easily within a complex protein compared with GFP and it might also be simpler to insert it into the genome using CRISPR. In the future, it will be interesting to determine if providing a long single‐strand DNA oligo (coding for the AID degron) as a simple donor for CRISPR will indeed result in very high efficiencies as reported for small genome manipulations . This may pave the way to AID‐targeted protein degradation in Drosophila going large scale.…”
mentioning
confidence: 99%